IMPACT OF GENERAL INSURANCE FINANCIAL RESULTS ON ECONOMIC GROWTH (BASED ON ECONOMETRIC MODELING) (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
The role of the general insurance industry in the country's insurance market and its importance in the socio-economic life of the population are mentioned in the article, as well as the impact of the financial results of the organizations operating in the general insurance industry on the country's gross domestic product was analyzed econometrically, and the impact on increasing the investment opportunities of insurance companies was studied.